2016
DOI: 10.14692/jfi.12.3.89
|View full text |Cite
|
Sign up to set email alerts
|

Ketahanan Berbagai Kultivar Padi Lokal terhadap Penyakit Hawar Daun Bakteri

Abstract: Bacterial leaf blight disease caused by Xanthomonas oryzae pv. oryzae is an important rice disease in Indonesia, including in South East Sulawesi. The use of resistant varieties is one of the effective and environmentally friendly control strategies to suppress the disease. This study aimed to determine the level of resistance of some local rice varieties of South and Southeast Sulawesi against Xanthomonas oryzae pv. oryzae pathotypes IV, VIII and X. The study was conducted in a screen house involving 3 bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…PCR detection targeting the cause of pepper yellow leaf curl disease, using Krusty-Homers primers, effectively detected PepYLCV, which indicated by DNA fragments around 580 bp (Figure 3). This result is similar to the previous study by Taufik et al [21], where a 580 bp begomovirusspecific DNA fragment was successfully amplified from plant samples. PCR detection using Krusty-Homers, showed that Red Habanero and F8 012328-6-2-1-1-3-1 were infected with PepYLCV.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…PCR detection targeting the cause of pepper yellow leaf curl disease, using Krusty-Homers primers, effectively detected PepYLCV, which indicated by DNA fragments around 580 bp (Figure 3). This result is similar to the previous study by Taufik et al [21], where a 580 bp begomovirusspecific DNA fragment was successfully amplified from plant samples. PCR detection using Krusty-Homers, showed that Red Habanero and F8 012328-6-2-1-1-3-1 were infected with PepYLCV.…”
Section: Resultssupporting
confidence: 92%
“…The extracted DNA is used as PCR template to determine if the method successfully obtained DNA. PepYLCV was detected using Krusty and Homers primers, which were used to detect Begomovirus envelope proteins [20,21]. DNA amplification was performed using NZYTaq II 2x Green Master Mix (Nzytech, Portugal) using 50ng/µL DNA, 1µM forward primers and 1µM reverse primers.…”
Section: Dna Verificationmentioning
confidence: 99%
“…Periode inkubasi pada beberapa kultivar padi lebih lama atau lebih cepat bergantung pada respons ketahanan pada setiap genotipe dan perkembangan penyakit (Khaeruni et al, 2014). Hasil penelitian lain diperoleh bahwa ketahanan padi lokal terhadap HDB strain IV, VIII, dan X, menunjukkan insidensi penyakit bervariasi antara 2,6 -77,6% sehingga reaksi ketahanan kultivar-kultivar padi lokal tersebut bervariasi dari rentan sampai sangat tahan (Khaeruni et al, 2016). Reaksi setiap tanaman berbeda, dengan tingkat kompetisi antara bakteri dan inang yang berbeda menyebabkan adanya interaksi yang berbeda pada setiap varietas.…”
Section: Pendahuluanunclassified
“…22 IRBB lines, five new high yielding varieties, 22 local varieties (Susanto and Sudir 2012), and some promising lines (Yuriyah et al 2013). Local rice varieties resistant to Xoo identified from Banten (Ali et al 2012), Sulawesi (Khaeruni et al 2016), and Aceh (Hadianto et al 2015). Although the resistance characteristics of released rice varieties showed to most dominant Xoo pathotypes, they might have no longer effective to control the BLB in the fields due to changing of new Xoo pathotypes (Sudir and Suprihanto 2006, Suprihatno et al 2010, Susanto and Sudir 2012, Khaeruni et al 2016.…”
Section: Introductionmentioning
confidence: 99%